2005
DOI: 10.1002/pbc.20453
|View full text |Cite
|
Sign up to set email alerts
|

Childhood ITP: 12 months follow‐up data from the prospective registry I of the Intercontinental Childhood ITP Study Group (ICIS)

Abstract: The high rate of recovery from ITP between 7 to 12 months demonstrates, that the cut-off point of 6 months for the definition of chronic ITP does not adequately differentiate chronic from acute ITP. The majority of children with ITP have variable time to recovery with gradual improvement of platelet counts and disappearance of bleeding signs. ITP is a heterogeneous disorder with a diverse natural history and diverse pattern of treatment response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
108
2
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(128 citation statements)
references
References 25 publications
11
108
2
7
Order By: Relevance
“…Our results concerning the acute and chronic patients were comparable with other series in terms of the incidence of clinical courses, mean/ median age at diagnosis, male/female ratio, initial PCs, and initial response rates to therapy [12][13][14][15]. At present, it is difficult to foresee at the time of diagnosis the patients who will develop a chronic course; although age older than 10 years, adoles- cence in females, and an initial PC >20x10 9 /L have been associated with a chronic course [12][13][14][15][16].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Our results concerning the acute and chronic patients were comparable with other series in terms of the incidence of clinical courses, mean/ median age at diagnosis, male/female ratio, initial PCs, and initial response rates to therapy [12][13][14][15]. At present, it is difficult to foresee at the time of diagnosis the patients who will develop a chronic course; although age older than 10 years, adoles- cence in females, and an initial PC >20x10 9 /L have been associated with a chronic course [12][13][14][15][16].…”
Section: Discussionsupporting
confidence: 77%
“…At present, it is difficult to foresee at the time of diagnosis the patients who will develop a chronic course; although age older than 10 years, adoles- cence in females, and an initial PC >20x10 9 /L have been associated with a chronic course [12][13][14][15][16]. In our study, initial PC >20x10 9 /L and initial diagnosis age >10 years were found to increase the probability of chronic outcome by at least two-fold (OR=2).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…10 Longer follow-up of the ICIS-I cohort published in 2006 suggests that a 6 month definition of chronic ITP may be too restrictive, since 25.6% of their 308 chronic ITP patients achieved a normal platelet count between 6 and 12 months after diagnosis. 11 Adult subjects are included in the current Pediatric and Adult Intercontinental Registry on Chronic ITP (PARC-ITP), and the UK ITP registries also enroll patients of all ages.…”
Section: Natural History Of Itp and Clinical Outcome Measuresmentioning
confidence: 99%
“…Severe bleeding is more likely to occur in children with platelet counts less than 50 × 10 9 /l. The incidence of intracranial hemorrhage in children with ITP is ~0.1-0.5% (9).…”
mentioning
confidence: 99%